Epidemiology of non-alcoholic fatty liver disease and risk of hepatocellular carcinoma progression - Chaitanya Thandra, Krishna; Barsouk, Adam; Saginala, Kalyan; Sukumar Aluru, John; Rawla, Prashanth; Barsouk, Alexander (Clinical and Experimental Hepatology, 2020)
Non-alcoholic fatty liver disease (NAFLD) has become the most common chronic liver disease worldwide. Its incidence has grown alongside the increasing global prevalence of type 2 diabetes, obesity, and metabolic syndrome. The risk of progression to hepatocellular carcinoma for nonalcoholic steatohepatitis patients over 5 years is 8%, and despite targeted and immunotherapy treatment advances, HCC maintains a bleak 5-year survival of 19%. NAFLD’s primary risk factors are components of metabolic syndrome as well as possible sleep disturbances. NAFLD is most common among men 50-60 years of age, though incidence in women catches up after menopause. In the US, Hispanics are most likely to develop NAFLD and African Americans least likely, in part due to the prevalence of the PNPLA3 gene variant. With NAFLD risk factors especially prevalent in underserved populations and developing nations, public health interventions, earlier diagnosis, and novel treatments could curb the growing disease burden.